A High-Precision Apparatus for the Characterization of Thermal Interface Materials - ROBINSON, ANTHONY (American Institute of Physics, 2009)
An apparatus has been designed and constructed to characterize thermal interface materials with unprecedented precision and sensitivity. The design of the apparatus is based upon a popular implementation of ASTM D5470 where well-characterized meter bars are used to extrapolate surface temperatures and measure heat flux through the sample under test. Measurements of thermal resistance, effective thermal conductivity, and electrical resistance can be made simultaneously as functions of pressure or sample thickness. This apparatus is unique in that it takes advantage of small, well-calibrated thermistors for precise temperature measurements 0.001 K and incorporates simultaneous measurement of electrical resistance of the sample. By employing precision thermometry, low heater powers and minimal temperature gradients are maintained through the meter bars, thereby reducing uncertainties due to heat leakage and changes in meter-bar thermal conductivity. Careful implementation of instrumentation to measure thickness and force also contributes to a low overall uncertainty. Finally, a robust error analysis provides uncertainties for all measured and calculated quantities. Baseline tests were performed to demonstrate the sensitivity and precision of the apparatus by measuring the contact resistance of the meter bars in contact with each other as representative low specific thermal resistance cases. A minimum specific thermal resistance of 4.68 10?6 m2 K/W was measured with an uncertainty of 2.7% using a heat transfer rate of 16.8W. Additionally, example measurements performed on a commercially available graphite thermal interface material demonstrate the relationship between thermal and electrical contact resistance. These measurements further demonstrate repeatability in measured effective thermal conductivity of approximately 1%
PUBLISHED
Keywords: Engineering